Inovasi Pembelajaran IPS: dari Hafalan ke Pemahaman, Selaras dengan Merdeka Belajar (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Learning Social Sciences (IPS) in Indonesia is still dominated by conventional methods based on memorization, so students often have difficulty connecting material with real life. Various studies have proposed learning innovations, but their implementation is still limited and poorly evaluated in the context of Merdeka Belajar. This research focuses on the implementation of social studies learning innovations at SDS Islam Ulul Albab which combines the role play method, the Teams Games Tournament (TGT) type cooperative learning model, and the use of audiovisual technology through Smart TV. The purpose of this study is to analyze the effectiveness of innovative methods in improving students' conceptual understanding without having to memorize. Using a qualitative approach with a field research method, data was collected through observation, interviews, and document analysis. The results showed that the role-playing method helped students understand social studies material through hands-on experience, while the TGT model increased students' participation and learning motivation through fun academic competition. In addition, the use of audiovisuals provides a more interesting learning experience and makes it easier for students to understand abstract social studies concepts. In conclusion, this learning innovation is effective in improving students' understanding conceptually, aligns with the principles of Merdeka Belajar, and has the potential to become a learning model that can be used to improve students' understanding of social studies.